2017
DOI: 10.3389/fpls.2016.02008
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Being First: Exploring Priority and Diversity Effects in a Grassland Field Experiment

Abstract: Diversity of species and order of arrival can have strong effects on ecosystem functioning and community composition, but these two have rarely been explicitly combined in experimental setups. We measured the effects of both species diversity and order of arrival on ecosystem function and community composition in a grassland field experiment, thus combining biodiversity and assembly approaches. We studied the effect of order of arrival of three plant functional groups (PFGs: grasses, legumes, and non-leguminou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 62 publications
2
75
3
Order By: Relevance
“…As a result, past events can have a strong impact on present plant communities (Grman & Suding, ; Vogelsang & Bever, ). One way past events can influence present plant communities is through priority effects, meaning that the order in which species arrive in an ecosystem can lead to different successional trajectories (Fukami & Nakajima, ; Weidlich, von Gillhaussen, Delory, et al., ). In our study system, disturbance by reindeer has been the driver that shifted the vegetation to a different community (causing a priority effect), which is now maintained through a series of altered biotic and abiotic feedbacks (historical contingency).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, past events can have a strong impact on present plant communities (Grman & Suding, ; Vogelsang & Bever, ). One way past events can influence present plant communities is through priority effects, meaning that the order in which species arrive in an ecosystem can lead to different successional trajectories (Fukami & Nakajima, ; Weidlich, von Gillhaussen, Delory, et al., ). In our study system, disturbance by reindeer has been the driver that shifted the vegetation to a different community (causing a priority effect), which is now maintained through a series of altered biotic and abiotic feedbacks (historical contingency).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the order and timing of plant species arrival after a disturbance event can have a long‐lasting impact on community assembly and shape the development of plant–soil feedbacks (Weidlich, von Gillhaussen, Delory, et al., ). So‐called historical contingency, which can be caused by plant–soil feedbacks, may lead to the formation of alternative vegetation states (Fukami, ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the evidence strongly suggests that if we want to have well‐functioning ecosystems that can be resistant or resilient especially in the face of climate change (Jaeschke et al ), we need to strive to have as many species with as many traits that differ from each other as possible in an ecosystem. Experiments that test the relevance of BEF outcomes for restoration have found that sowing more diverse seed mixtures (Bullock et al , ) or altering the order of arrival of plant functional groups (Weidlich et al , ) can lead to more productive but also diverse plant communities. This is an asset within extensively managed grasslands, since higher biodiversity is usually mutually exclusive to provisioning of crops and commodities in intensive agriculture (Cord et al ).…”
Section: Stepping Up To Create a Broad Scientific Basis For Large‐scamentioning
confidence: 99%
“…There is now an expanding body of literature claiming that the creation of priority effects would be a useful technique to restore degraded habitats, alter competitive relationships, and steer plant communities towards desirable states in terms of biodiversity and functioning (Wilsey et al 2015;Temperton et al 2016;Weidlich et al 2017Weidlich et al , 2018Young et al 2017). Manipulating plant community assembly to promote native species that will ultimately exert strong priority effects on exotics is also a very interesting approach to lower the risk of invasion (Hess et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In grasslands, priority effects caused by biotic interactions can have effects that supersede abiotic influence on the community. Priority effects caused by species arriving before others can affect community structure as well as ecosystem functioning both aboveground (Wilsey et al 2015;Weidlich et al 2017) and belowground (Körner et al 2008;Weidlich et al 2018). Such priority effects occur either because the early-arriving species reduce the amount of resources available for late-arriving species (called niche preemption) (Fukami 2015), or because the early-arriving species modified the type of niches available for the species arriving later via, for instance, extra nitrogen (N) availability if N2-fixing species arrive first, root exudation or the selection of a particular soil microbiome (called niche modification, including plant-soil feedbacks) Suding et al 2013;van der Putten et al 2013;Perkins & Hatfield 2014;Fukami 2015).…”
Section: Introductionmentioning
confidence: 99%